(untitled) (Physical Education, Health and Social Sciences, 2025)
This study examines the impact of financial literacy (FL) and digital financial literacy (DFL) on the digital payment behaviour of Generation Y in Pakistan. With the increasing reliance on online financial transactions, understanding how financial literacy shapes consumer behaviour is critical for fostering financial stability and inclusion. A quantitative research approach was employed, using a structured survey to collect data from 200–250 Millennials. Regression analysis was conducted to assess the relationship between financial literacy, digital payment systems, and consumer behaviour. The results indicate that digital financial literacy has a stronger influence on the adoption of digital payment systems than traditional financial literacy. Millennials with higher digital financial literacy demonstrate greater trust in digital financial services, leading to more effective financial management. However, concerns regarding security risks and financial illiteracy continue to hinder widespread adoption of digital payment systems. The study underscores the need for integrating digital financial education into financial literacy programs. Policymakers, financial institutions, and fintech companies should focus on enhancing security measures and expanding financial literacy initiatives to encourage greater adoption of digital payment systems. This research provides insights into the role of digital financial literacy in shaping consumer behaviour within the Pakistani context. By addressing security concerns and enhancing financial education, financial institutions can foster more informed financial decision-making and improve financial inclusion.